2013
DOI: 10.1016/j.tet.2013.04.114
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed C–H arylation using aryltrifluoroborates in conjunction with a MnIII oxidant under mild conditions

Abstract: This paper describes the development of a mild Pd-catalyzed C–H arylation reaction using potassium aryltrifluoroborates in conjunction with Mn(OAc)3 as the oxidant. The scope of this transformation is explored with a variety of different aryltrifluoroborates and arylpyridine substrates. Preliminary mechanistic studies suggest that the reaction proceeds via a high-valent Pd mechanism with C–H activation occurring at or before the rate determining step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Later on, Sanford and co‐workers reported a mild palladium‐catalysed CH arylation of 2‐arylpyridines using potassium aryltrifluoroborates in conjunction with Mn(OAc) 3 as an oxidant (Scheme ) 31. They found that ArBF 3 K species bearing electron‐withdrawing and electron‐donating groups were tolerant to these reaction conditions; and moderate to high yields (52–80%) were obtained when electron‐neutral and electron‐rich ArBF 3 K species were used as substrates.…”
Section: Metal‐catalyzed Cross‐coupling Via Single Ch Bond Activationmentioning
confidence: 99%
“…Later on, Sanford and co‐workers reported a mild palladium‐catalysed CH arylation of 2‐arylpyridines using potassium aryltrifluoroborates in conjunction with Mn(OAc) 3 as an oxidant (Scheme ) 31. They found that ArBF 3 K species bearing electron‐withdrawing and electron‐donating groups were tolerant to these reaction conditions; and moderate to high yields (52–80%) were obtained when electron‐neutral and electron‐rich ArBF 3 K species were used as substrates.…”
Section: Metal‐catalyzed Cross‐coupling Via Single Ch Bond Activationmentioning
confidence: 99%
“…For example, as seen for the diazidation procedure, the halomethyl substituted substrates 1 j,o afforded the expected products 3 j,o and the methallyl sulfonamides 1 k,l reacted satisfactorily under the standard conditions. [30] In search of evidences to propose plausible mechanisms for these transformations, the following considerations were taken into account: a) although Mn-(OAc) 3 -promoted alkene azidations are known, [31] our protocol provides the azidation only with the associated presence of catalytic Pd(OAc) 2 ; b) Pd-catalyzed alkene azidations are known when carried out in the presence of strong terminal oxidants; [32] c) recent studies suggest that Mn(OAc) 3 can oxidize Pd(II) complexes to high valent complexes; [33] d) an ad-hoc experiment carried out in the presence of stoichiometric amounts of Pd(OAc) 2 , but in the absence of Mn(OAc) 3 , gave only degradation products (Scheme 4, protocol A, B); e) the experiments carried out in the presence of the radical scavenger TEMPO suggested the involvement of radical intermediates in the mechanism (Scheme 4, protocol C, D); [34] f) tertiary N-allyl sulfonamides proved to be unreactive in the standard reaction conditions (Scheme 4, protocol E).…”
Section: Table 2 Diazidation Of N-allyl Sulfonamides [Ab]mentioning
confidence: 99%